2019
DOI: 10.1002/adfm.201904268
|View full text |Cite
|
Sign up to set email alerts
|

Toxico‐Metabolomics of Engineered Nanomaterials: Progress and Challenges

Abstract: Nanoscale matter has unique attributes that potentiate their widespread application from biomedicine, engineering, food, cosmetics, sensing, to energy. Due to the rapid industrialization of engineered nanomaterials (ENMs) as a result of increasing consumer interests, more ENMs will be released into the environment, greatly increasing the probability of their contact with humans. Once these ENMs enter the human body or an ecosystem, they may initiate various biochemical responses in unprecedented ways, thus rai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 246 publications
(261 reference statements)
0
23
0
Order By: Relevance
“…Metabolomics is a powerful tool to evaluate the effects of nanomaterials on human cells 42 44 as it allows the detection of metabolic changes that cannot be quantified by other techniques. An NMR-based metabolomics approach was previously used to demonstrate that low concentrations of GO and FLG (5 µg/mL) induce metabolic changes in HaCaT cells 23 .…”
Section: Resultsmentioning
confidence: 99%
“…Metabolomics is a powerful tool to evaluate the effects of nanomaterials on human cells 42 44 as it allows the detection of metabolic changes that cannot be quantified by other techniques. An NMR-based metabolomics approach was previously used to demonstrate that low concentrations of GO and FLG (5 µg/mL) induce metabolic changes in HaCaT cells 23 .…”
Section: Resultsmentioning
confidence: 99%
“…Despite the rapid developments in these fields, there remain a number of challenges in nanotechnology development. The key issues are the health risk and safety concern of ENPs, especially in the field of nanomedicine (Susan et al, 2018;Ahmad et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the rapid developments in these fields, there remain a number of challenges in nanotechnology development. The key issues are the health risk and safety concern of ENPs, especially in the field of nanomedicine ( Susan et al, 2018 ; Ahmad et al, 2019 ). Numerous studies have reported the ENP-associated toxicity to zebra fish ( Lakshmi et al, 2019 ; Bakshi, 2020 ), macroalgae ( Sfriso et al, 2019 ), animals ( Jia et al, 2017 ; Teng et al, 2019 ), and even human beings ( Guo et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…This review aimed to deliver a comprehensive view of AgNPs for diagnostics and therapeutic treatment of several cancer genomes and metabolomes from multi-omics technology (i.e., genomics, transcriptomics, proteomics, and metabolomics). The multi-omics sciences have globally matured to target structural, molecular, and phenotypic changes in systems biology [142,143]. Here, we have carefully accounted for the variability of several genomes, proteomes, and metabolomes which are mostly highly listed in terms of AgNPs-based targeting therapy in tumor microenvironmental locations.…”
Section: Conclusion Challenges and Future Perspectivesmentioning
confidence: 99%